Design of a mincer of cactus and agave leaves - Pulido-Delgado, Jose Luis; Duran García, Héctor Martin; Ávila Galarza, Alfredo; Vasilevich Krasnoschekova, Yuri; Vladimirovna Krasotina, Larisa (Acta Universitaria, 2021)
A design of a mincer machine to cut agave leaves and cactus prickly cladodes to a length of 2 cm to 3 cm, able to fulfill the silage conditions (25% dry matter and much less space for air), was made. When developing the slicing tool for the machine that will successfully perform the cut of maguey leaves and cactus prickly cladodes, knowledge about measurements of key physical properties from the plants was needed. T here was also a detailed static and dynamic analysis for the interaction between knife-vegetation mass-hardship. Moreover, it was determined the slicing force, feeding direction and suction capacity for the vegetation mass performed by the working tool, as well as the speed and power for cutting. Care was taken to continuously separate the end cubed product from the fresh mass entering. Results showed that the technological process undertaken by the machine was highly satisfactory regarding the objective and that the size from the end material is adequate for silage and ready for cattle consumption.